Analysis of vertical reinforcement in slender reinforced concrete (tilt-up) panels with openings & subject to varying wind pressures - Bartels, Brian D. (Kansas State University, 2010)
This report offers a parametric study analyzing the vertical reinforcement for slender reinforced concrete walls (tilt-up panels) subject to 90 miles per hour (mph), 110 mph, 130 mph, and 150 mph three-second gust wind speeds. Wall panel heights of 32 feet (ft) and 40 ft are considered for one-story warehouse structures. First, solid tilt-up panels serve as the base design used in the comparison process. Next, square openings of 4 ft, 8 ft, 12 ft, and 16 ft centered in the wall panel, are analyzed. A total of 32 tilt-up panel designs are conducted, establishing the most economical design by the least amount of reinforcement and concrete used. In addition to lateral wind pressures, the gravity loads acting on the load bearing tilt-up panel are dead load, roof live load, and snow load. All loads for this report are determined based on a typical 24 ft by 24 ft bay. The procedure to design the tilt-up panels is the Alternative Design of Slender Walls outlined in the American Concrete Institute standard ACI 318-08 Building Code Requirements for Structural Concrete and Commentary Section 14.8 In general, an increase in panel height, lateral wind pressure, and/or panel openings, requires an increase in reinforcement to meet strength and serviceability. Typical vertical reinforcement in tilt-up panels is #4, #5, and #6 size reinforcement bars. A double-mat reinforcement scheme is utilized when the section requires an increase in reinforcement provided by use of a single-layer of reinforcement. A thicker tilt-up panel may be needed to ensure tension-controlled behavior. Panel thicknesses of 7.25 inches (in), 9.25 in, and 11.25 in are considered in design.
Keywords: tilt-up concrete panels; slender reinforced concrete panels; Architecture (0729)